A critical review on bioremediation technologies for Cr(VI)-contaminated soils and wastewater. Issue 12 (18th June 2019) - Xia, Shaopan; Song, Zhaoliang; Jeyakumar, Paramsothy; Shaheen, Sabry M.; Rinklebe, Jörg; Ok, Yong Sik; Bolan, Nanthi; Wang, Hailong
Abstract: Chromium (Cr) is a potentially toxic metal originating from natural processes and anthropogenic activities such as the iron-steel, electroplating, and leather industries, which is carcinogen to living organisms and has an ecological risk. Hence, research into the remediation of Cr pollution has attracted widespread attention. Bioremediation techniques have advantages of causing little disturbance to soil and water, low cost, simple and convenient operation, and less secondary pollution. In this review, we briefly describe the chemical properties of Cr, sources of Cr pollution, environmental quality, toxicological/health effects of Cr, and analytical methods. We also discuss the factors that govern methods for the bioremediation of Cr and compare their advantages and disadvantages. In particular, we focus on efforts to establish Cr bioremediation processes and their mechanisms. The main mechanisms include biosorption, bioaccumulation, complexation, electrostatic attraction, Cr(VI) reduction to Cr(III), and ion exchange, which decrease the Cr(VI) concentrations and convert Cr(VI) into Cr(III) lowering its toxicity and making it environmentally benign. However, bioremediation is still a challenging technique and most studies remain at the laboratory stage. Therefore we suggest areas for future research and provide theoretical guidance and a scientific basis for the application of biosorbents for Cr(VI) bioremediation in soils and wastewater.